Impact of Rhythm vs. Rate Control in Atrial Fibrillation on the Long-Term Outcome of Patients Undergoing Transcatheter Edge-to-Edge Mitral Valve Repair - Christian Waechter (MDPI AG, 2021)
Atrial fibrillation (AF) is a highly prevalent comorbidity in patients with severe mitral valve regurgitation (MR) undergoing transcatheter mitral valve repair (TMVR) and has been shown to significantly worsen their outcome. However, data on the impact of AF treatment strategy in this rapidly growing cohort of patients is unknown. In a multicenter, observational cohort study, 542 consecutive patients undergoing TMVR were enrolled, and subsequently, comprehensive survival analyses according to AF status and therapy were performed using propensity score matching and Cox regression. In the analyzed cohort, 373 (73.3%) of the TMVR patients had concomitant AF. Of these patients, 212 (59%) were on rate control therapy and 161 (41%) were on rhythm control therapy. At 3 years, significantly reduced cumulative survival was observed for patients on rhythm compared to patients on rate control (46.7% (75/161) vs. 56.5% (91/161), p = 0.032). Amiodarone was used to a substantial extent for rhythm control and found to be an independent mortality predictor (Hazard Ratio 1.5, 95%CI 1.1–2.1, p = 0.04). The adverse outcome of concomitant AF in TMVR patients was confirmed (AF: 47.3% (126/266) vs. non-AF: 58.3% (78/133), p = 0.047). Rhythm control achieved almost exclusively pharmacologically is associated with an adverse outcome compared to the rate control of AF in TMVR. This raises awareness of the importance of AF and its treatment, as this seems to be a promising key point for improving the prognosis of TMVR patients.